Close-kin marriage – An injustice to forthcoming generations - Joybell, C Chrishantha; Kumar, M Kawin (Eastern Journal of Medical Sciences, 2020)
Consanguineous marriage is the union between two individuals who are related as second cousins or closer and who have a common ancestor. There are various contributing factors to these marriages, namely, economic, cultural, social factors, and cultural isolation. Many societies nowadays do not allow marriages between close relatives, perhaps as a result of observations on the progeny of consanguineous marriages and the fear of unhealthy offsprings. This review article mainly intends to throw light on the genetic abnormalities caused by consanguineous marriages. It aspires to reveal the mystery behind the uncut diamonds sparkling as healthy children.